(untitled) (Journal of Fiber Bioengineering and Informatics, 2009)
There are a growing number of children and babies diagnosed with multi sensory disability and visual impairment. Developing and stimulating these children is often done in Multi Sensory rooms in schools and hospitals where the child can experience visual, tactile, olfactory, auditory, motor, cognitive and communicatory toys and products. Many of these aids use plastic coatings for ease of cleaning between multiple users but have limited textures, however the work reported here investigates the role of textiles as a learning aid, exploring different surfaces and effects to enhance the tactile sensations of an object and concluding in a ball being designed and developed almost entirely from textiles. The techniques and technology included in the product are; UV florescent dyestuffs, ‘Shibori’ technique, colour changing fibre optics, retro reflective materials and microencapsulated aroma and anti-bacterial technology. A limited case study has been undertaken and demonstrates the success of the product. The use of texture, light and aroma together with movement gives a lot of stimulation to a child. Teachers involved with the project gave positive feedback on how the child responded.